Clinical utility of FDG PET/CT for primary and recurrent papillary renal cell carcinoma - Guozhu Hou; Dachun Zhao; Yuanyuan Jiang; Zhaohui Zhu; Li Huo; Fang Li; Wuying Cheng (Cancer Imaging, 2021)
Abstract Purpose Papillary renal cell carcinoma (RCC) is the second most common subtype of RCC, after clear cell RCC. This study aimed to investigate the usefulness of FDG PET/CT in primary and recurrent papillary RCC, and the role of staging FDG PET/CT in predicting survival. Methods A total of 66 patients with histopathologically confirmed papillary RCC who underwent either staging or restaging FDG PET/CT scans (30 had staging scans only, 28 had restaging scans only, 8 had both) were retrospectively included in this study. The sensitivity and specificity of restaging FDG PET/CT for detecting recurrence were assessed by histopathology and/or clinical follow-up as standard reference. Results Staging FDG PET/CT scans were performed in 38 patients, of which 31 (81.5%) showed FDG-positive primary renal lesions. The SUVmax of high-grade (WHO grade 3 and 4) papillary RCCs were significantly higher than that of low-grade (WHO grade 1 and 2) tumors (9.44 ± 6.18 vs 4.83 ± 3.19, P = 0.008). The SUVmax was not significantly different between type 1 and type 2 papillary RCCs (5.71 ± 2.88 vs. 6.99 ± 5.57, P = 0.563). Of the 38 patients, 12 developed disease progression during the follow-up period. Patients with primary tumor SUVmax> 5.85 were associated with significantly shorter progression-free survival (PFS) than those with tumor SUVmax≤5.85 (P = 0.005). Restaging FDG PET/CT scans were performed in 36 patients with suspected recurrent papillary RCCs. FDG PET/CT showed a sensitivity and specificity of 100 and 72.7% for detecting recurrent disease. Comparison of PET/CT scans with CT/MRI imaging was available in 23 patients. FDG PET/CT revealed additional findings in 11 patients, mainly including lymph node and bone metastases. FDG PET/CT findings led to change in management in 5.3% (2/38) of patients in the staging setting and 16.7 (6/36) of patients in the restaging setting. Conclusions FDG PET/CT had a sensitivity of 81.5% for detecting primary papillary RCC, and tumor SUVmax derived from staging FDG PET/CT was a predictor of PFS. In the restaging process of papillary RCC, FDG PET/CT was very effective for detecting recurrent disease.